KRZYSZTOF BRZECHCZYN (ed.), Towards a Revival of Analytical Philosophy of History. Around Paul A. Roth’s Vision of Historical Sciences: Leiden –Boston 2018, Brill (Poznań Studies in the Philosophy of the Sciences and the Humanities 110), 304 s. - Šima, Karel (Dějiny – teorie – kritika, 2019)
Review.